Regulation of DNA replication initiation by ParA is independent of parS location in Bacillus subtilis. Issue 10 (27th October 2022) - Koh, Alan; Strahl, Henrik; Murray, Heath
Abstract : Replication and segregation of the genetic information is necessary for a cell to proliferate. In Bacillus subtilis, the Par system (ParA/Soj, ParB/Spo0J and parS ) is required for segregation of the chromosome origin ( oriC ) region and for proper control of DNA replication initiation. ParB binds parS sites clustered near the origin of replication and assembles into sliding clamps that interact with ParA to drive origin segregation through a diffusion-ratchet mechanism. As part of this dynamic process, ParB stimulates ParA ATPase activity to trigger its switch from an ATP-bound dimer to an ADP-bound monomer. In addition to its conserved role in DNA segregation, ParA is also a regulator of the master DNA replication initiation protein DnaA. We hypothesized that in B. subtilis the location of the Par system proximal to oriC would be necessary for ParA to properly regulate DnaA. To test this model, we constructed a range of genetically modified strains with altered numbers and locations of parS sites, many of which perturbed chromosome origin segregation as expected. Contrary to our hypothesis, the results show that regulation of DNA replication initiation by ParA is maintained when a parS site is separated from oriC . Because a single parS site is sufficient for proper control of ParA, the results are consistent with a model where ParA is efficiently regulated by ParB sliding clamps following loading at parS .